Conjugated Dienyl Derivatives by Green Bisallylic Substitution: Synthetic and Mechanistic Insight. Issue 14 (27th June 2016) - Cazorla, Clément; Billamboz, Muriel; Chevrin‐Villette, Carole; Hapiot, Frédéric; Monflier, Eric; Len, Christophe
Abstract: The first palladium‐catalyzed bisallylic substitution on biobased bisallylic derivatives was explored. The developed method, performed under green conditions with microwave irradiation, led to valuable conjugated dienes. The mechanism was studied by ESI‐MS and NMR spectroscopy, which highlighted the involvement of bis‐π‐allylpalladium complexes in the catalytic cycle. Abstract : All‐yl for one and one for all‐yl : 1 H NMR and 31 P NMR spectroscopy and ESI‐MS analyses tend to prove the involvement of palladium bis‐π‐allyl complexes during the nucleophilic bisallylic substitution of biosourced hexa‐1, 5‐diene‐3, 4‐diacetate. This catalytic and recyclable reaction is performed under green conditions under microwave irradiation and affords valuable conjugated dienyl derivatives with a high selectivity for the E / E isomers (DCM=CH2 Cl2 ).